Estudo do comportamento de juntas de argamassa reforçadas com fibras de polipropileno - Araújo, Cícero Thiago Figueiredo de (2005)
In this work the connection behavior between precast elements using cement mortar with polypropylene fibers addition is studied to evaluate its performance when compression loads is applied. A numerical analysis with the finite elements program ANSYS 7.1® was made considering mortars range from 0% to 50% of polypropylene fibers addition. The numerical model considered in the analysis was composed of two reinforced concrete blocks with 10x10x20cm dimensions, joined between themselves by a cement mortar with marble and granite residue addition, developed in laboratory, which will receive polypropylene fibers addition. The numerical analysis was later validated by an experimental program. With the gotten results, it was evidenced that lower than 3% tax fibers propitiated better performance of the joint and, consequently, of the model. A profit in the horizontal and vertical deformation capacity was observed prorroguing the mortar splitting in the model, which makes high system strength capacity, resulting in an increase of the connection ductility. Between 4% and 10% the model kept any behavior alteration and from 15%, it started to lose strength and rigidity. The experimental models had presented load capacity profit with fibers addition and similar cracked ways of numerical model and the models observed in literature. However 2% fibers taxes higher were not possible to investigate because a lower workability performance had been gotten.